Assessment of air quality and indoor environmental condition for potential workers' dormitory within Singapore shipyard - Lim, Ivan You Feng. (2013)
Growing population in Singapore is a great concern and there is a steady trend of increasing foreign workers over the decades. Utilisation of land by housing shipyard workers (high percentage foreigners) in dormitories within shipyard is an attractive option; therefore a study was performed to assess the air quality and indoor environmental conditions of the dormitories. The report aims to quantify the various air quality parameters such as PM, heavy metal content and VOCs to ascertain the feasibility to house workers within the dormitories.